Media Language in Time of Political Crisis: values’ study of sample of program show "Fi Dairat Al-Daou'a" - جعفر محمد (International Journal of Social Communication, 2022)
The study focuses on values' approach to media language in times of political crises, by knowing the extent to which values ​​are present in the language of "Fi Dairat Daou’a" program broadcasting on the Algerian TV channel during its coverage of the political crisis in Algeria on February 22, 2019. It was based on the value determinism theory as a theoretical approach and used the survey method. The researcher conducted a content analysis of purposive sample of eight-television show. Our results Indicate that the causes of the crisis in Algeria are primarily political, and that the most important values ​​in the language of the “Fi Dairat Al-Daou'a” program were political values.